Integrated versus incidental dental care in nursing homes. (21st November 2012) - Gerritsen, P.F.M.; van der Bilt, A.; Cune, M.S.; Schrijvers, A.J.P.; de Putter, C.
ABSTRACT: Purpose/aim: In most of the 334 Dutch nursing homes, incidental dental care is provided upon indication by the medical and nursing staff. However, more and more nursing homes offer integrated dental care, where a dentist works on a structural basis in facilities within the home. Methods: To evaluate the costs and effects of integrated versus incidental care, we studied the oral status and treatment needs in two nursing homes in the same city with 175 and 120 residents an average age of 81.7 and 79.3 years, respectively. Results: In the integrated care home, the dentist spent an average 2.2 hours/year per resident at a cost of €229 for the dentist's work and €143 for laboratory costs. In the incidental care home, these values were 0.1 hours/year per resident at a cost of €15 for the dentist's work and €20 for laboratory costs. Conclusions: With integrated care, 55.6% of the residents had no oral treatment need versus 13.1% for incidental care, more edentulous residents wore dentures, and residents had less soft tissue pathology.